Study on the Antioxidant Compounds Extracted from Longan (Dimocarpus longan Lour.) Shell - Hong Li, Zhen; Min Wang, Qiao; Ming Pan, Ying (Asian Journal of Chemistry, 2014)
Further study on the antioxidant activity of ethanol extracts of longan shell has been explored. Seven compounds have been separated from the main active fractions. The structures of these compounds were identified by nuclear magnetic resonance and mass spectroscopy. They were isovanillin (1), scopoletin (2), quercetin (3), hyperin (4), astragalin (5), b-phenylethyl alcohol (6) and piperine (7). The antioxidant activities of these compounds were measured and compared with the main active fractions. It was found that quercetin and hyperin performed excellent antioxidant activities and proved the antioxidant activity of longan shell extract.